2020
DOI: 10.1136/bmjspcare-2020-002580
|View full text |Cite
|
Sign up to set email alerts
|

Professionals guidance about palliative medicine in chronic heart failure: a mixed-method study

Abstract: IntroductionHealthcare professionals (HCPs) experience difficulties in timely recognising and directing palliative care (PC) needs of their patients with chronic heart failure (CHF). The aim of this study was to develop a comprehensive tool to enable HCPs in timely recognising and directing PC needs in CHF.MethodsA four-stage mixed-method study was performed. Stage 1: identification of needs and questions of patients and families; stage 2: prioritisation and refinement of the needs and questions; stage 3a: tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“… 32 For patients with heart failure, the I-HARP has recently been developed. 33 Finamore et al attempted to cluster patients with COPD by their symptoms, which could be a first step to development of such a tool specific for COPD. 34 However, due to limited time and financial resources, it is not attainable to provide a comprehensive person-centered assessment to all patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“… 32 For patients with heart failure, the I-HARP has recently been developed. 33 Finamore et al attempted to cluster patients with COPD by their symptoms, which could be a first step to development of such a tool specific for COPD. 34 However, due to limited time and financial resources, it is not attainable to provide a comprehensive person-centered assessment to all patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The development of the original "I-HARP" has been described previously (Ament et al 2020). In short, the original "I-HARP" consisted of opening questions to start exploring palliative care needs followed by identification questions to identify palliative care needs.…”
Section: The Original "I-harp"mentioning
confidence: 99%
“…A study about palliative care for people with dementia has shown that easily disseminated conversation tool tailored to disease-specific elements increased the confidence of HCPs in initiating and discussing palliative care (Berry et al 2023). Previously, the research team developed such a conversation tool for patients with chronic heart failure (CHF), called "I-HARP" (Identification of patients with HeARt failure with palliative care needs) (Ament et al 2020). This original "I-HARP" supports HCPs to timely recognize, discuss, and direct palliative care needs of Dutch patients with CHF.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, people with HF experience physical symptoms such as breathlessness, fatigue, and poor appetite. 5 Informal caregivers of patients also experience poor outcomes such as increased psychosocial distress and poor well-being, 6 with a negative impact on their quality of life.…”
mentioning
confidence: 99%
“…Despite improvements in treatment, the outcomes in patients with HF remain poor, and this has consequences not only for patients with HF but also for their caregivers. Indeed, people with HF experience physical symptoms such as breathlessness, fatigue, and poor appetite 5 . Informal caregivers of patients also experience poor outcomes such as increased psychosocial distress and poor well-being, 6 with a negative impact on their quality of life.…”
mentioning
confidence: 99%